Mangrove vegetation in Amazonia: a review of studies from the coast of Pará and Maranhão States, north Brazil - MENEZES, Moirah Paula Machado de (Instituto Nacional de Pesquisas da Amazônia, 2014)
The present study is a compilation of the literature about vegetation of mangrove forest of the north coast of Brazil. It synthesizes the knowledge about this important ecosystem and lists the currently available literature. The study focuses on the coast of Pará and Maranhão states, which are covered by a continuous belt of mangroves. The mangrove flora comprises six mangrove tree species and several associated species. Mangrove tree height and stem diameter vary as a function of abiotic local stand parameters. Seasonal variation in rainfall and salinity affect the species' phenology and litter fall. Local population use products derived from mangrove plants for different purposes (e.g. fuel; medicinal; rural construction). The increase in the coastal population has given rise to conflicts, which impact on mangrove forest.